ANALISIS MULTI KRITERIA DALAM PEMILIHAN UNIT PENGOLAHAN AIR IPA CIAWI, KECAMATAN MEGAMENDUNG, KABUPATEN BOGOR - Riana Ayu Kusumadewi; Ratnaningsih Ratnaningsih; Hildegard Gabrielle (Jurnal Lingkungan dan Kota, 2022)
To increase service coverage and meet the increasing demand for drinking water, PDAM Tirta Kahuripan plans to build a Ciawi WTP in Megamendung District with a processing capacity of 165 L/second using the Sukabirus River as a raw water source. The purpose of this study was to determine the processing units in the design of the Ciawi WTP using multi-criteria analysis. Based on the results of the analysis of raw water quality, there were several parameters that do not meet the drinking water quality standards according to the Minister of Health Regulation No. 492 of 2010 and PPRI No. 82 of 2001, namely turbidity, Fecal coliform, total coliform, TSS, BOD, COD, and DO. There were three alternative processing circuits used. Alternative I consists of intake, hydraulic coagulation, up-down flow hydraulic flocculation, plate settler sedimentation, rapid sand filtration, disinfection, and reservoir. Alternative II consists of intake, hydraulic coagulation, vertical-shaft paddle wheel mechanical flocculation, tube settler sedimentation, rapid sand filtration, disinfection, and reservoir. Alternative III consists of intake, in-line static mixers coagulation, horizontal-shaft paddle wheel mechanical flocculation, plate settler sedimentation, rapid sand filtration, disinfection, and reservoir. There are other factors that must be considered in the selection of treatment units, namely contaminant removal, reliability, flexibility, construction, land requirements, ease of operation, maintenance, cost, and environmental compatibility. Based on multi-criteria analysis, the percentage of suitability for alternative I is 78%, Alternative II is 63%, and Alternative III is 48%. From this assessment, it can be said that alternative I is the best alternative.